Reference Ranges for Hematological and Biochemical Profile of Martina Franca Donkeys - Trimboli, Francesca; De Amicis, Ippolito; Di Loria, Antonio; Ceniti, Carlotta; Carluccio, Augusto (Frontiers in Veterinary Science, 2020)
The Martina Franca donkey (MFd) is one of the largest Italian donkey breeds, considered as endangered breed. To support the conservation strategies, knowledge about the physiologic hematological parameters of MFds is needed. The aims of the study were to determine reference value for hematological and major serum parameters in a population of healthy MFds and to estimate the influence of age on these parameters. Eighty-one clinically healthy MFds (17 males and 64 females) in different ages were enrolled: group A (foals, n° 16, animals < 1 year old) group B (young animals, n° 36, from 1 to 3 years old), and group C (adult animals, n° 29, over 3 years old). Red blood cell count (RBC); hematocrit value (HCT); hemoglobin concentration (HGB); mean corpuscular volume (MCV); mean corpuscular hemoglobin (MCH); hemoglobin concentration distribution width (HDW); RBC distribution width (RDW); total white blood cell (WBC); WBC differential count for neutrophils, lymphocytes, monocytes, eosinophils and basophils, and platelets (PLT); mean platelet volume (MPV); platelet volume distribution width; and plateletcrit (PCT) were analyzed. The biochemistry panel included aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma glutamyl transferase (GGT), total serum protein (TP), albumin (ALB), cholesterol (CHOL), triglyceride (TGL), blood urea nitrogen (BUN), creatinine (CREA), glucose (GLU), Ca2+, phosphorus, Na+, Cl−, K+, and Mg2+. The effect of age on hematological parameters was investigated using one-way ANOVA test. Age of donkeys does not influence total WBC, HGB, HCT, platelet count and MPV, and PCT (P > 0.05). Some leukocyte populations such as eosinophils, monocytes, and basophils showed age-linked variations (P < 0.05). RBC count, RDW, and HDW decrease with age whereas MCV and MCH increase. Na+, K+, Cl−, Ca2+, phosphorus, ALP, GGT, CREA, GLUC, and CHOL decrease with age (P < 0.05), while AST and TP showed an increase with aging (P < 0.05). ALB reaches the lowest values in young donkeys and returns to values of foals in older animals (P < 0.05). Finally, a difference among groups for BUN and TGL was not found (P < 0.05). The results suggest how even for the MFd breed, age is a variable that affects different hematological and biochemical parameters. Compared to other donkey and horses, the MFd breed showed some differences that clinicians involved during conservation strategies need to be consider.